The Urgency of Regulating Funding Sources Under the Supervision of Land Title Officials in Indonesia - Azhar Ravif; Mohammad Hamidi Masykur; R. Imam Rahmat Sjafi'i (Indonesian Journal of Law and Syariah, 2026)
This research aims to identify the incompleteness of regulations in Ministerial Regulation Number 2 of 2018 concerning the Guidance and Supervision of Land Title Officials. The regulation does not concretely address the sources of funding and the honorarium entitled to those who perform additional duties to carry out the guidance and supervision required by the regulation. As a result, this lack of clarity may hinder the effective implementation of policies and lead to potential disparities in how Land Title Officials are compensated for their responsibilities. This research has a problem formulation in the form of, "How urgent is the regulation of funding sources in the coaching and supervision of Land Title Officials?" This type of research is normative juridical, with research approaches including the statute approach and conceptual approach. The research results indicate that there is an incompleteness in the regulations regarding funding sources and honorariums for the Supervisory and Supervisory Council of Land Title Officials, and the urgency of regulating funding sources is to create legal certainty, especially related to state financial regulations that require these rules to be strictly regulated.